Circular economy in the 3D printing construction industry: a design, durability, materials, and processes solution to achieve decent, affordable, and sustainable housing in Nuevo León and Mexico - Mendoza Rangel, José Manuel; Zapata Padilla, José Raúl; Anguiano Pérez, Francisco David; Velásquez Hernández , Mario Iván; Mares Chávez, Samuel; Espino Robles, Erik Eduardo; Alvarado López, Joel Isaac; López Serna, Michael Adrián; Mendoza Jiménez, José Alberto; Díaz Aguilera, Jorge Humberto (Revista ALCONPAT, 2024)
This review of 3D-printing of cementitious materials (3DPCM) evaluates its suitability to build Decent, Affordable and Sustainable Housing (DASH) in Mexico, considering mechanical requirements, durability, and sustainability. The climate and economic crises are current challenges for a Circular Construction Industry, but the 3DPCM reduces CO2 emissions, materials and waste, labor, times and costs by up to 88%, 50%, 70% and 90%, respectively, achieving the strength and durability of conventional construction. Likewise, there are 3DPCM companies in developed countries, but importing this technology to developing countries is not affordable, therefore, research into 3DPCM technologies is ongoing in Nuevo León, Mexico, allowing the construction of DASH for 1,700-4,500/m2.